Dermoscopy of squamoid eccrine ductal carcinoma: an aid for early diagnosis - Márcio Martins Lobo-Jardim; Bruno de Castro e Souza; Priscila Kakizaki; Neusa Yurico Sakai Valente (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Squamoid eccrine ductal carcinoma is a cutaneous malignancy that originates from the eccrine sweat gland. A 76-year-old woman presented with an asymptomatic papule on her nose that had been present for one year. Dermoscopy showed pseudocysts, irregular linear crown vessels, and yellowish-brown globules surrounded by white halos. This is the first dermoscopic description of squamoid eccrine ductal carcinoma. Studies with more cases are needed to confirm the dermoscopic characterization of this tumor.